FAKTOR RISIKO DERMATITIS KONTAK PADA PEKERJA: ANALISIS BERDASARKAN USIA, MASA KERJA, DAN PENGGUNAAN APD - Tri Puspita Prihatinningrum AF (Nusantara Hasana Journal, 2025)
Contact dermatitis is one of the skin diseases that often occurs in workers due to exposure to irritants or allergens in the workplace. Risk factors such as age, length of service, length of contact, history of atopy, personal hygiene, and use of Personal Protective Equipment (PPE) play an important role in the occurrence of contact dermatitis. Analyzing the relationship between risk factors and the occurrence of contact dermatitis in workers. Methods: An observational study was conducted on 66 workers with secondary data analysis from the master table. The variables studied included age, gender, length of service, length of contact, history of atopy, personal hygiene, and use of PPE. Most workers with contact dermatitis were ≥30 years old (78.8%), had a length of service ≥2 years (89.4%), and did not use PPE according to standards (77.3%). A positive history of atopy was found in 28.8% of cases. The use of PPE that did not meet standards, age ≥30 years, and length of service ≥2 years were the dominant factors contributing to contact dermatitis. Interventions in the form of training in the use of PPE and regular monitoring of worker health are needed.